The Effect of The treatment of Kanguru Method on Increse Weight in low Born Weight - Fatmawati, Nurul; Zulfiana, Yesvi; Ulya, Yadul (STIKES Yarsi Mataram, 2021)
The incidence of low birth weight (LBW) is estimated at 15% of all births in the world with a range of 3.3% - 38% and is more common in developing countries or low socioeconomic conditions. Statistically, 90% of LBW incidence is found in developing countries and the mortality rate is 35 times higher than that of babies with birth weight of more than 2500 grams. LBW mortality rate in Indonesia is still high, around 27 per 1000 live births. LBW requires optimal care. Low Birth Weight (LBW) is the weight of a baby born less than 2,500 grams. The aim of this study was to examine the effect of kangaroo care on weight gain in low birth weight babies. This study is a literature review that attempts to explore the effect of kangaroo treatment on weight gain in low birth weight infants. Results from 5 articles show the significant results of kangaroo treatment on weight gain in low birth weight babies. It is suggested for mothers to apply the kangaroo treatment method as an effort that can be used to increase body weight at low birth weight newborns. In addition to increasing body weight, the kangaroo method can also increase oxygen saturation because an upright baby position can optimize respiratory function which is influenced by earth gravity so that it has an effect on the baby's ventilation and perfusion